Design and construction of a fibre interferometer for the study of MEMS and NEMS to temperatures below 1 K - Patton, Mark James (2013)
Optical interferometry offers a powerful tool for the study of the mechanical motion of micro- and nano-electromechanical systems (MEMS and NEMS). By examining the modulation of reflected light the displacement can be measured with sub-nanometre precision. Recent work with fibre interferometers carried out by other groups has studied the motion of nanomechanical systems down to temperatures as low as 1 K.